Forensic Accounting as A Tool for Detecting and Preventing Financial Fraud in South West Nigeria (Journal of Management and Social Sciences, 2026)
Financial fraud poses a significant threat to the economic stability of organisations and nations. In Nigeria, cases of financial fraud have led to massive losses, affecting both public and private sectors. Forensic accounting has emerged as a critical tool for detecting and preventing financial fraud. This study investigates the effectiveness of forensic accounting in combating financial fraud in Nigeria. Using a descriptive survey approach, data were collected from 350 respondents, including accountants, auditors, and financial managers. A self-structured questionnaire was used, and its reliability was tested using the test-retest method, yielding a reliability coefficient of 0.82. Data were analysed using one-way analysis of variance (ANOVA). The findings revealed that forensic accounting significantly enhances fraud detection and prevention. It was concluded that adoption of forensic accounting enhances transparency, accountability, and trust in financial systems, and organisations that leverage forensic accounting are better equipped to identify and mitigate fraudulent activities, thereby safeguarding their resources. It was recommended that organisations integrate forensic accounting practices into their financial systems and train staff to improve fraud detection capabilities.  Keywords     Forensic accounting, financial fraud, fraud detection, fraud prevention